2020
DOI: 10.3390/en13226044
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing COVID-19 Impacts on Vehicle Travels and Daily Nitrogen Dioxide (NO2) Levels among Florida Counties

Abstract: The COVID-19 outbreak and ensuing social distancing behaviors resulted in substantial reduction on traffic, making this a unique experiment on observing the air quality. Such an experiment is also supplemental to the smart city concept as it can help to identify whether there is a delay on air quality improvement during or after a sharp decline on traffic and to determine what, if any, factors are contributing to that time lag. As such, this study investigates the immediate impacts of COVID-19 causing abrupt d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“… Citation Geographic locations COVID19 related intervention Confounding adjustment Statistical approach Results Berman et al 22 United States (all counties in the U.S. with both NO 2 and PM 2.5 monitors) Reduced traffic and mandated business closures between March 13-April 21. March 13th being when U.S. reported cases exceeded 2000 and the first enacted state-wide social distancing order None Two-sided t-tests paired by county (α = 0.05) 25.5% reduction (4.8 ppb) in NO 2 was observed during the COVID-19 period NO 2 decline was statistically significant regardless of when mandated business closures were implemented 11.3% statistically significant reduction (0.7 μg/m 3 ) of PM 2.5 in counties from states that instituted early non-essential business closures Gillingham et al 28 (Commentary) United States (785 monitors) Shutdowns Weather and seasonality Global polynomial and a two-step local regression PM 2.5 concentrations have decreased by around -0.5 μg/m 3 since the start of the shutdowns Estimated 11% NOx decrease in daily local emissions There is insufficient evidence to prove that there was a significant decrease in PM 2.5 concentrations in the U.S Goldberg et al 24 20 cities in North America COVID-19 Physical distancing measures (lockdown) (15 March to 30 April post-covid-19 period) Solar zenith angle and meteorological conditions over very short time scales Average differences Adjusted for seasonality and meteorology, NO 2 had a median drop of 21.6% before and after COVID‐19 physical distancing Karaer et al 25 Florida COVID-19 social distancing behaviors (March 2020) Population density and income A cross-correlation based dependency analysis …”
Section: Introductionmentioning
confidence: 99%
“… Citation Geographic locations COVID19 related intervention Confounding adjustment Statistical approach Results Berman et al 22 United States (all counties in the U.S. with both NO 2 and PM 2.5 monitors) Reduced traffic and mandated business closures between March 13-April 21. March 13th being when U.S. reported cases exceeded 2000 and the first enacted state-wide social distancing order None Two-sided t-tests paired by county (α = 0.05) 25.5% reduction (4.8 ppb) in NO 2 was observed during the COVID-19 period NO 2 decline was statistically significant regardless of when mandated business closures were implemented 11.3% statistically significant reduction (0.7 μg/m 3 ) of PM 2.5 in counties from states that instituted early non-essential business closures Gillingham et al 28 (Commentary) United States (785 monitors) Shutdowns Weather and seasonality Global polynomial and a two-step local regression PM 2.5 concentrations have decreased by around -0.5 μg/m 3 since the start of the shutdowns Estimated 11% NOx decrease in daily local emissions There is insufficient evidence to prove that there was a significant decrease in PM 2.5 concentrations in the U.S Goldberg et al 24 20 cities in North America COVID-19 Physical distancing measures (lockdown) (15 March to 30 April post-covid-19 period) Solar zenith angle and meteorological conditions over very short time scales Average differences Adjusted for seasonality and meteorology, NO 2 had a median drop of 21.6% before and after COVID‐19 physical distancing Karaer et al 25 Florida COVID-19 social distancing behaviors (March 2020) Population density and income A cross-correlation based dependency analysis …”
Section: Introductionmentioning
confidence: 99%
“…Using the travel data in China, Kraemer et al, 2020 , Chinazzi et al, 2020 found that travel restrictions issued by the Chinese government have reduced the spread of COVID-19 in that country. Regarding travels in the United States, a study by Karaer et al (2020) showed that COVID-19 reduced vehicle travels in all Florida counties, which resulted in a significant reduction in traffic. Finally, Yilmazkuday (2020) focused on inter-county travels and found that strict restrictions on travels across counties in the United States reduced the number of new cases and new deaths.…”
Section: Introductionmentioning
confidence: 99%
“…These include particulate matter with aerodynamic diameter less than 2.5 μm (PM 2.5 ), nitrogen and sulfur dioxides (NO 2 and SO 2 , respectively), carbon monoxide (CO), and ozone (O 3 ). NO 2 is a primary pollutant that is mainly produced from vehicular emissions, and has therefore exhibited wide reductions during the lockdowns ( Hoang et al, 2021 ), as evident from ground-level measurements ( Berman and Ebisu, 2020 ; Zangari et al, 2020 ) and remote sensing data ( Karaer et al, 2020 ; Elshorbany et al, 2021 ). CO is also a primary pollutant, emitted directly due to combustion, that has displayed a decline in its concentrations during the lockdowns ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a few studies have attempted to characterize the impact of the COVID-19 pandemic lockdowns on air quality in the state. However, these were conducted either by using remote sensing data ( Elshorbany et al, 2021 ; Karaer et al, 2020 ), or on a relatively low temporal resolution (Bekbulat et al, 2021), or focused primarily on few criteria pollutants (e.g., Karaer et al, 2020 ). Hence, these studies lack the capability to explain the overall processes that govern air quality on a city level.…”
Section: Introductionmentioning
confidence: 99%